An evaluation of a long-term breeding programme in a closed Sahiwal herd in Kenya. I. Effects of non-genetic factors on performance and genetic parameter estimates - Rege, J.E.O.; Lomole, M.A.; Wakhungu, Judi W. (Wiley, 1992)
Investigates the effects of non genetic factors on performance, and estimates genetic parameters of reproductive and productive traits with a view to examining the appropriateness of the assumed parameters. Presents an evaluation of a long-term breeding programme in a closed Sahiwal herd in Kenya and presents data on means, standard deviations and coefficients of variation for the traits studied. The present breeding management at the Sahiwal stud requires that heifers be mated when they are 27 months old and are weighing between 260 to 270 kg. The estimate of mean age at first calving indicates that heifers were not able to attain the required weight until they were over 29 months. Indeed the age-weight requirement is unrealistic and is partially responsible for late age at first calving. In addition to this, there is a lower-than-expected growth rate at the stud. However, the increased age at first calving may also be a reflection of poor heat detection. Poor feeding is likely to affect age at first calving through its effect on growth rate and hence age at puberty. Moreover, nutritionally - induced silent heat may not only affect service period and calving interval but, through its effect on age at first service, does also affect age at first calving. The mean calving interval of 426d was shorter than reported for the Sahiwal breed in India, but was longer than for Bos taurus breeds in Kenya and elsewhere. However, most reported estimates of calving intervals for indigenous breeds have been in herds using natural mating.